(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
In the article, the indicators of targeted development of the insurance market of Uzbekistan in the future are analyzed and their classification is presented. Scientific conclusions and recommendations on the further improvement of the country’s insurance market have been formulated.